On the origin of the dramatic spectral variability of WPVS 007. Issue 4 (20th May 2019) - Li, Junyao; Sun, Mouyuan; Wang, Tinggui; He, Zhicheng; Xue, Yongquan
ABSTRACT: We report the discovery of large-amplitude mid-infrared variabilities (MIR; ∼0.3 mag) in the Wide-field Infrared Survey Explorer W 1 and W 2 bands of the low-luminosity narrow-line Seyfert 1 galaxy WPVS 007, which exhibits prominent and varying broad-absorption lines (BALs) with blueshifted velocity up to 14 000 km s^-1 . The observed significant MIR variability, the UV to optical colour variabilities in the Swift bands that deviate from the predictions of pure dust attenuation models, and the fact that Swift light curves can be well fitted by the stochastic AGN variability model suggest that its observed flux variabilities in the UV–optical–MIR bands should be intrinsic, rather than owing to variable dust extinction. Furthermore, the variations of BAL features (i.e. trough strength and maximum velocity) and continuum luminosity are concordant. Therefore, we propose that the BAL variability observed in WPVS 007 is likely induced by the intrinsic ionizing continuum variation, alternative to the rotating-torus model proposed in a previous work. The BAL gas inWPVS 007 might be in the low-ionization state as traced by its weak N v BAL feature; as the ionizing continuum strengthens, the C iv and Si iv column densities also increase, resulting in stronger BALs and the emergence of high-velocity components of the outflow. The outflow launch radius might be as small as ∼8 × 10 −4 pc under the assumption of being radiatively driven, but a large-scale origin (e.g. torus) cannot be fully excluded because of the unknown effects from additional factors, e.g. the magnetic field.